A utilização do DSD (digital smile design) para a otimização da estética dental - Moura, Amanda Pontes de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The DSD (digital smile design) nowadays has been using as great resource for aesthetic restorative dentistry. Using software can be facilitate and implement through of simulations aesthetics rehabilitation treatment, making the pacient has a better understanding of the procedure and results, and lower misunderstandings that occur in other aesthetic rehabilitative options. This technique consists of analyzing facial and dental proportions of each patient and the relations with their teeth, lips and gum through digital photograph and movies. Therefore designs are made following specific methods that can be presented in a simple way, understandable and engaging for the patient

O DSD (digital smile design), tem sido na atualidade um recurso de grande destaque para a odontologia reabilitadora estética. O uso de software pode facilitar e implementar através de simulações o tratamento reabilitador estético, fazendo com que haja maior entendimento do paciente sobre o procedimento e resultado, bem como menores equívocos que ocorrem em outras opções reabilitadoras estéticas . A técnica consiste em analisar as proporções faciais e dentárias de cada paciente e suas relações com dentes, lábios e gengivas por meio de fotografias digitais e vídeos. Com isso, são realizados desenhos seguindo métodos específicos que podem ser apresentados de maneira simples, compreensível e cativante para o paciente
Keywords: Estética dentária; Fotografia dentária; Reabilitação bucal; Esthetics, Dental